Nuclear fusion: half a century of magnetic confinement fusion research - Braams, C. M. (Institute of Physics Pub., 2011)
Fusion research started over half a century ago. Although the task remains unfinished, the end of the road could be in sight if society makes the right decisions. Nuclear Fusion: Half a Century of Magnetic Confinement Fusion Research is a careful, scholarly account of the course of fusion energy research over the past fifty years. The authors outline the different paths followed by fusion research from initial ignorance to present understanding. They explore why a particular scheme would not work and why it was more profitable to concentrate on the mainstream tokamak development. The book features descriptive sections, in-depth explanations of certain physical and technical issues, scientific terms, and an extensive glossary that explains relevant abbreviations and acronyms.